Metis: a fast integrated tokamak modelling tool for scenario design. (16th August 2018) - Artaud, J.F.; Imbeaux, F.; Garcia, J.; Giruzzi, G.; Aniel, T.; Basiuk, V.; Bécoulet, A.; Bourdelle, C.; Buravand, Y.; Decker, J.; Dumont, R.; Eriksson, L.G.; et al.
Abstract: METIS is a numerical code aiming at fast full tokamak plasma analyses and predictions. It combines 0D scaling-law normalised heat and particle transport with 1D current diffusion modelling and 2D equilibria. It contains several heat, particle and impurities transport models, as well as heat, particle, current and momentum sources, which allow faster than real time scenario simulations. This paper gives a first comprehensive description of the METIS suite: overall structure of the code, main available models, details on the simulation workflow and numerical implementation. Some examples of applications to the analysis of experimental discharges and the predictions of ITER scenarios are also given.